2014
DOI: 10.1088/0004-637x/795/2/108
|View full text |Cite
|
Sign up to set email alerts
|

Ogle-Ing the Magellanic System: Stellar Populations in the Magellanic Bridge

Abstract: We report the discovery of a young stellar bridge, that forms a continuous connection between the Magellanic Clouds. This finding is based on number density maps for stellar populations found in data gathered by OGLE-IV, that fully cover over 270 deg 2 of the sky in the Magellanic Bridge area. This is the most extensive optical survey of this region up to date. We find that the young population is present mainly in the western half of the MBR, which, together with the newly discovered young population in the e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 40 publications
4
83
0
Order By: Relevance
“…Bagheri, Cioni & Napiwotzki (2013);Skowron et al (2014);Noël et al (2015) all present evidence of an older population of stars throughout the Bridge based on CMD analyses. The OGLE observations support this as well, with the presence of RR Lyrae variables in the Bridge confirming the residence of an old (at least 10 Gyr) stellar population.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Bagheri, Cioni & Napiwotzki (2013);Skowron et al (2014);Noël et al (2015) all present evidence of an older population of stars throughout the Bridge based on CMD analyses. The OGLE observations support this as well, with the presence of RR Lyrae variables in the Bridge confirming the residence of an old (at least 10 Gyr) stellar population.…”
Section: Discussionmentioning
confidence: 89%
“…By examining the Bridge between the LMC and SMC, we gain insight into the structure of the system and their history of interactions. Studies have shown that the young and intermediate age stars in the MB have a clumpy, non-uniform distribution (Noël et al 2013(Noël et al , 2015Skowron et al 2014). The asymmetric locations of these stellar populations suggest that either they formed in situ or were stripped from the LMC or the SMC during an interaction.…”
Section: Extinction Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the age, metallicity and reddening, we searched for solutions in the following ranges: 6.60 < log(τ /yr)< 10.00 (steps of 0.05); 0.0001 < Z < 0.0020 (steps of ∼ 0.002); 0.00 < E(B − V ) < 0.30 (steps of 0.01). Once again, these ranges are sufficiently wide to cover any result concerning the SMC or the Bridge, like the ones present in the SMC age-metallicity determinations for stellar clusters (Piatti 2011;Parisi et al 2014) and field stellar populations (Carrera et al 2008;Rubele et al 2015), in the analysis of Bridge field stars (Nidever et al 2013;Skowron et al 2014), and reddening maps (Burstein & Heiles 1982;Schlegel, Finkbeiner & Davis 1998).…”
Section: Methods Of Analysismentioning
confidence: 98%
“…Earlier studies by Demers & Battinelli (1998) and Harris (2007) did not find the presence of intermediate-age/old stellar populations in fields centred on the H i ridge line of the MB. However, recent studies (Bagheri, Cioni & Napiwotzki 2013;Noël et al 2013Noël et al , 2015Skowron et al 2014) found evidence of the presence of intermediate-age/old stellar populations in the central and western regions of the MB.…”
Section: Introductionmentioning
confidence: 99%